Discourses on Sanctity and Mithology Around The Popularity of Mount Batur Area in Climbing Tours - I Gede Mudana; I Ketut Sutama; Cokorda Istri Sri Widhari (Soshum: Jurnal Sosial dan Humaniora, 2018)
Mountains in Bali are believed by the local people to have power of sanctity. In Mount Batur, Kintamani District, Bangli Regency, such a sanctity has a close relationship with mithology that developed not only in Batur, Kintamani, and Bangli but also Bali in general. On the other hand, Mount Batur is one of the most popular mountains in Bali as a climbing/trekking arena especially when Mount Agung as the highest mountain is experiencing eruption at this time. There are about 300 climbing/trekking tourists who climb and descend Mount Batur every day. This qualitative study was conducted to determine the aspects of sanctity and mythology around the popularity of Mount Batur area in climbing tours. Its data is analyzed by qualitative data analysis technique through data reduction, data presentation, and conclusion and its result is descriptively presented. The results of the study indicate that the values ​​of Mount Batur's sanctity are associated with the mountain’s niskala (divine) relation with Batur Lake, Ulun Danu Batur Temple, and even Mount Agung in Karangasem Regency which all are sacred lake, temple, and mountain which. In connection with the sanctity, there is a mythology, such as myths, legends, fairy tales, and folklore. Mount Batur as a beautiful and exotic volcano is much liked by climbing/trekking tourists moreover Lake Batur, Ulun Danu Batur Temple, and Mount Agung located near the mountain are also interesting tourist attractions, with their own sanctity and mythology